Antagonism of Nitrogen Fertilizer and Rhizobium on Growth, Nodulation and Yield Of Peanuts (Arachis hypogaea L.) on Acid Soil - Setyaningrum, Desy; Supriyono, Supriyono; Putri, Riza Noermala (PLANTA TROPIKA, 2025)
Acid soil is widely available in Indonesia and is suboptimal, so yields are low. The research examines the effect of antagonism and nitrogen fertilizer on peanuts' growth, nodulation, and yield in sour planting. This study used a factorial complete randomized block design with two factors. The first factor is the dose of Nitrogen fertilizer with four levels: 0, 50, 100, 150 kg.ha-1. The second factor is the source of rhizobium with three levels: without rhizobium, legin rhizobium dose ten g.kg-1 seed, and rhizobium from peanut plantations. They were repeated three times. Nitrogen 50 kg.ha-1 with the source of used peanut rhizobium showed the highest plant height, 15.73 cm. The combination of 100 kg.ha-1 of nitrogen with a source of used peanut rhizobium showed the highest number of plant leaves, namely 675.33 leaves. A nitrogen dose of 50kg.ha-1  produced the highest effective number of nodules and nodules, namely 363.00 and 19.33 nodules. The optimum nitrogen fertilizer dose is 44 kg.ha-1 for nodule growth. 50 kg.ha-1  nitrogen dose produced the highest number of pods and seed weight, namely 48.67 pods and 407.79 g of seeds. Nitrogen fertilizer at the correct dose can increase peanuts' growth, nodulation, and yield in acid soil. However, a dose that is too high may cause antagonism with the nodulation process and reduced yield.